Systems metabolic insights into kaempferol-mediated alleviation of alcoholic fatty liver disease - Song, Chenmeng; Li, Lijia; Li, Jia; Yao, Jengyuan (Frontiers in Endocrinology, 2025)
IntroductionAlcoholic fatty liver disease (AFLD) is a significant global health concern caused by chronic and excessive alcohol consumption, leading to hepatic steatosis, inflammation, and metabolic disruption. Currently, there are limited effective therapeutic options. Kaempferol, a dietary flavonoid, has shown potential for regulating oxidative stress and lipid metabolism.MethodsIn this study, C57BL/6 mice (n = 12 per group) were assigned to control, ethanol-fed (AFLD), or ethanol plus kaempferol (KPF) groups. The AFLD model was induced using a modified Lieber-DeCarli diet with stepwise ethanol escalation and a final single binge dose. Kaempferol was administered at 20 mg/kg/day by gavage. Serum biochemical markers, liver histology, oxidative stress indices, and untargeted plasma metabolomics were assessed to evaluate KPF’s protective effects.ResultsKaempferol-treated mice exhibited significantly reduced alanine aminotransferase (ALT, p < 0.0001) and aspartate aminotransferase (AST, p < 0.05) levels compared to the AFLD group. Histological analysis revealed improved hepatic architecture and reduced lipid droplet accumulation. Kaempferol also enhanced antioxidant capacity, evidenced by reduced malondialdehyde (MDA, p < 0.05). Metabolomic profiling identified multiple altered metabolites associated with glycolysis, amino acid metabolism, and sphingolipid signaling.DiscussionThese findings indicate that kaempferol exerts protective effects against AFLD through multi-target regulation of oxidative stress and metabolic pathways. Our study provides systems-level evidence supporting kaempferol as a promising dietary-based intervention for AFLD management.